In-vivo and in-vitro environments affect the storage and release of energy in tendons - Bossuyt, Fransiska M.; Leonard, Timothy R.; Scott, W. Michael; Taylor, William R.; Herzog, Walter (Frontiers in Physiology, 2024)
Understanding tendon mechanical properties, such as stiffness and hysteresis, can provide insights into injury mechanisms. This research addresses the inconsistency of previously reported in-vivo and in-vitro tendon hysteresis properties. Although limited, our preliminary findings suggest that in-vivo hystereses (Mean ± SD; 55% ± 9%) are greater than in-vitro hystereses (14% ± 1%) when directly comparing the same tendon for the same loading conditions in a sheep model in-vivo versus within 24 h post-mortem. Overall, it therefore appears that the tendon mechanical properties are affected by the testing environment, possibly related to differences in muscle-tendon interactions and fluid flow experienced in-vivo versus in-vitro. This communication advocates for more detailed investigations into the mechanisms resulting in the reported differences in tendon behaviour. Overall, such knowledge contributes to our understanding of tendon function towards improving modelling and clinical interventions, bridging the gap between in-vivo and in-vitro observations and enhancing the translational relevance of biomechanical studies.